ANALISA FASILITAS INFRASTRUKTUR TERMINAL AIVIDJAN DI KABUPATEN KEEROM - Widiyaningsih, Asti; Rante, Harmonis; Wakarmamu, Thobby (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2024)
Aividjan Terminal is Keerom Regency's largest terminal. This terminal is located in Arso District, which is the center of regional activities (PKW) in Keerom Regency and serves as a Type B terminal classification. Aividjan Terminal has been in operation since 2015, but until now, it has not been functioning properly. The Aividjan Terminal, which was supposed to be a transit point or transfer hub for public transportation coming from the villages of each district and continuing on to Jayapura City, is not functioning properly. In fact, the Aividjan terminal is situated along the main road between Jayapura City and Keerom Regency. The Aividjan terminal integrates with the self-managed goods distribution market in Keerom Regency, a crucial hub for the community, particularly for trade and agricultural product distribution from the villages. The terminal is not working as expected, according to ground facts. The purpose of this research is to analyze the completeness of the infrastructure facilities at the Aividjan terminal to determine whether they meet the classification of type B terminals according to the Directorate General of Land Transportation. We conducted the research through field observation analysis, assessing the completeness of the infrastructure facilities at the Aividjan terminal against the standards set by the Directorate General of Land Transportation of the Republic of Indonesia. The analysis results reveal that the Aividjan terminal has only fulfilled 14 out of 40 requirements, or just 35%, of the terminal facility requirements stated by the Directorate General of Land Transportation.